Prêts syndiqués en DTS : Une comparaison entre deux facilités bancaires - Leroux, François (Études internationales, 1984)
Five of the most important currencies compose the SDR, the currency cocktail which is. at the base of the International Monetary System. Violent swings on the foreign exchange markets and greatest uncertainty of interest rates plead for a more frequent use of currency cocktails international operators. Both the Ecu and the SDR should have been more present in international finance. This article presents and analyses two international transactions in which the SDR was selected as unit of account: the first one is a syndicated loan to the Kingdom of Sweden and the second one a syndicated loan to the Republic of the Ivory Coast. A comparison of the two credits is presented and their differences are exposed. The author concludes that the SDR could be, in practice, very different from a private transaction to the next. Additional clauses are required when a currency cocktail is selected for a euro-credit : the definition of the SDR, the definition of the dollar-value of the SDR, the difficulty of the calculation of the interest rates, the problems of foreign exchange quotations make additional clauses necessary. As a consequence, the documentation of a SDR credit is more complex than in the case of a classic US dollar facility.